Induction of Apoptosis in Candida albicans by Semi-purified Fraction of Hypnea musciformis - R, Mary Santhi (Asian Journal of Biological and Life Sciences)
The leading cause of death worldwide is microbial infections. Amidst the rise of new species of Candida, Candida albicans leads the list with high morbidity and mortality rates. One of the most opportunistic pathogens responsible for infectious diseases in human beings is Candida albicans. To overcome this problem, there is a need to explore new antifungals that could replace the current treatment options. Marine red alga Hypnea musciformis was collected from the coastal areas of Rameswaram. The collected alga was cleaned, shade-dried, and powdered and extraction was done using the Soxhlet apparatus. The crude methanolic extract was subjected to bioassay-guided silica gel chromatography. A total of six fractions was obtained, among the six fractions, the fifth fraction was subjected to time killing assay, biofilm reduction assay and phosphatidylserine externalization against Candida albicans. The aim of the current study was to evaluate the potential of a semipurified fraction of Hypnea musciformis to induce apoptosis in Candida albicans. In time killing assay, 1× and 2× MIC concentrations within 4 to 6 hr, the fungal cells were eradicated rapidly. The corresponding MIC values are required to reduce 50% of the biofilm’s metabolic activity 30-2000 times. From the results, it was evident that the SPF of H. musciformis exhibited good antibiofilm activity. SPF induced the production and accumulation of intracellular ROS, which finally induces apoptotic features in C. albicans, was confirmed using Annexin V double staining assay.
Keywords: Candida albicans; FITC – Annexin V; Phosphatidylserine; ROS